2018
DOI: 10.1371/journal.pone.0189668
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for tissue engineering of the tendon-bone interface

Abstract: The tendon-bone interface (enthesis) is a highly sophisticated biomaterial junction that allows stress transfer between mechanically dissimilar materials. The enthesis encounters very high mechanical demands and the regenerative capacity is very low resulting in high rupture recurrence rates after surgery. Tissue engineering offers the potential to recover the functional integrity of entheses. However, recent enthesis tissue engineering approaches have been limited by the lack of knowledge about the cells pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
(57 reference statements)
1
19
0
1
Order By: Relevance
“…Together, these results support the hypothesis that the direct crosstalk between differentiated and stem cells within the system can potentiate fibrochondrogenic commitment characteristic of the chondrocyte-like phenotype observed for native enthesis cells [15]. Furthermore, conditioned media from parallel cultures of fibroblastsonly, osteoblasts-only, and fibroblast-osteoblast co-culture were collected and added to monocultures of BMSCs to evaluate the effect of paracrine communication [66].…”
Section: Co-culture Of Terminally Differentiated Cells With Stem Cellssupporting
confidence: 73%
See 1 more Smart Citation
“…Together, these results support the hypothesis that the direct crosstalk between differentiated and stem cells within the system can potentiate fibrochondrogenic commitment characteristic of the chondrocyte-like phenotype observed for native enthesis cells [15]. Furthermore, conditioned media from parallel cultures of fibroblastsonly, osteoblasts-only, and fibroblast-osteoblast co-culture were collected and added to monocultures of BMSCs to evaluate the effect of paracrine communication [66].…”
Section: Co-culture Of Terminally Differentiated Cells With Stem Cellssupporting
confidence: 73%
“…A direct co-culture model with hTDCs and pre-OBs (1:1 cell ratio) was then established. [15,16] and the use of an optimal culture condition that can maintain different phenotypes at the same time is a major advantage supporting the combination of stem cells with differentiated cells.…”
Section: Co-culture Of Terminally Differentiated Cells With Stem Cellsmentioning
confidence: 99%
“…Cells are depicted cyan (scale bar = 150 μm). Image adapted from Kuntz et al (2018) (reproduced with permission under the terms of the CC BY 4.0 license. Copyright 2018, PLOS Publishing).…”
Section: Main Tissues Of the Musculoskeletal Systemmentioning
confidence: 99%
“…2 C) [ 18 , 25 ]. Recently, Kuntz et al presented a transcriptomic study at the tendon-to-bone interface and identified several interface biomarkers by combining transcriptomics with proteomics, which provides a bench-mark to study whether the differentiation of seeded MSCs towards a physiological phenotype [ 29 ]. However, the precise identification of the cell subpopulations at the interface remains unknown.…”
Section: The Structure and Composition Of Enthesismentioning
confidence: 99%